Low-grade oncocytic tumor of the kidney—a clinical, pathological, and next generation sequencing-based study of 20 tumors - Alex Jenei; Boglárka Pósfai; Borbála Dénes; Áron Somorácz; Gertrud Forika; Attila Fintha; Zsófia Mészáros; Noémi Kránitz; Tamás Micsik; Kornélia Veronika Eizler; Nándor Giba; Dávid Semjén; et al. (Pathology and Oncology Research)
Low-grade oncocytic tumor (LOT) of the kidney is a recently recognized renal neoplasm with distinctive morphologic, immunophenotypic, and molecular features that distinguish it from other eosinophilic tumors such as oncocytoma and chromophobe renal cell carcinoma (chRCC). This study presents a comprehensive analysis of 20 LOTs from 19 patients, integrating clinicopathological, immunohistochemical, and genetic data. LOTs typically appeared as small, unilateral, well-circumscribed tumors with a tan-brown cut surface, composed of uniform eosinophilic cells with round nuclei and occasional perinuclear halos. Key histological hallmarks included an extensive capillary network and central edematous areas without necrosis or significant atypia. Immunohistochemically, all tumors showed strong diffuse CK7 positivity and CD117 negativity, with universal expression of GATA3, GPNMB, and L1CAM. Whole-exome and panel-based sequencing revealed recurrent mutations in the mTOR signaling pathway, including MTOR, TSC1, and ATM genes. mTORC1 activation was confirmed immunohistochemically in one case. No evidence of aggressive behavior or metastasis was observed during the follow-up period (median: 4.5 years). Comparative analysis demonstrated that LOT patients were diagnosed at an older age than those with chRCC and had smaller tumors overall. This study reinforces the notion that LOT is a distinct renal tumor entity with consistent morphology, immunoprofile, and mTOR-pathway-related genetic alterations. Despite overlapping features with other eosinophilic renal neoplasms, the specific immunohistochemical profile and indolent clinical course support LOT’s classification as a unique diagnostic category.